On the likelihood of future eruptions in the Chilean Southern Volcanic Zone: interpreting the past century's eruption record based on statistical analyses - Dzierma,Yvonne (Servicio Nacional de Geología y Minería (SERNAGEOMIN), 2012)
A sequence of 150 explosive eruptions recorded during the past century at the Chilean Southern Volcanic Zone (SVZ) is subjected to statistical time series analysis. The exponential, Weibull, and log-logistic distribution functions are fit to the eruption record, separately for literature-assigned volcanic exploslvlty indices (VEI) ≥ 2 and VEI ≥ 3. Since statistical tests confirm the adequacy of all the fits to describe the data, all models are used to estimate the likelihood of future eruptions. Only small differences are observed between the different distribution functions with regard to the eruption forecast, whereby the log-logistic distribution predicts the lowest probabilities. There is a 50% probability for VEI ≥ 2 eruptions to occur in the SVZ within less than a year, and 90% probability to occur within the next 2-3 years. For the larger VEI ≥ 3 eruptions, the 50% probability is reached in 3-4 years, while the 90% level is reached in 9-11 years.